Krieg und Kunst im antiken Griechenland und Rom Heldentum, Identität, Herrschaft, Ideologie - Hölscher, Tonio (Münchner Vorlesungen zu Antiken Welten, 2019)
Images of war in Greek and Roman art reveal much more than the mere veneration of victory and glory. This book examines ancient Greek and Roman sculpture and memorials to reveal the ambivalent motivating forces that underlie the violence of war to this day: individual heroism, political identity, universal rule, and imperial ideology.